Comparison Between Minimally Invasive and Open Gastrectomy for Gastric Cancer in Europe: A Systematic Review and Meta-analysis. (March 2017) - Kostakis, I. D.; Alexandrou, A.; Armeni, E.; Damaskos, C.; Kouraklis, G.; Diamantis, T.; Tsigris, C.
Aims: We compared laparoscopic and robotic gastrectomies with open gastrectomies and with each other that were held for gastric cancer in Europe. Methods: We searched for studies conducted in Europe and published up to 20 February 2015 in the PubMed database that compared laparoscopic or robotic with open gastrectomies for gastric cancer and with each other. Results: We found 18 original studies (laparoscopic vs open: 13; robotic vs open: 3; laparoscopic vs robotic: 2). Of these, 17 were non-randomized trials and only 1 was a randomized controlled trial. Only four studies had more than 50 patients in each arm. No significant differences were detected between minimally invasive and open approaches regarding the number of retrieved lymph nodes, anastomotic leakage, duodenal stump leakage, anastomotic stenosis, postoperative bleeding, reoperation rates, and intraoperative/postoperative mortality. Nevertheless, laparoscopic procedures provided higher overall morbidity rates when compared with open ones, but robotic approaches did not differ from open ones. On the contrary, blood loss was less and hospital stay was shorter in minimally invasive than in open approaches. However, the results were controversial concerning the duration of operations when comparing minimally invasive with open gastrectomies. Additionally, laparoscopic and robotic procedures provided equivalent results regarding resection margins, duodenal stump leakage, postoperative bleeding, intraoperative/postoperative mortality, and length of hospital stay. On the contrary, robotic operations had less blood loss, but lasted longer than laparoscopic ones. Finally, there were relatively low conversion rates in laparoscopic (0%–6.7%) and robotic gastrectomies (0%–5.6%) in most studies. Conclusion: Laparoscopic and robotic gastrectomies may be considered alternative approaches to open gastrectomies for treating gastric cancer. Minimally invasive operations are characterized by less blood loss and shorter hospital stay than open ones. In addition, robotic procedures have less blood loss, but last longer than laparoscopic ones.